effets de l'amendement en gypse et en DS sur les caractéristiques physico-chimiques et hydriques d'un sol salé d'EL Hmadena ( RELIZANE) - Saadoune, Fatma Zohra (My University, 2016)
Salinization and sodisation are identified as a major process of degradation of irrigated soils in arid and semi-arid areas. The conduct of irrigation and hydro-agricultural development may, in large measures, minimize salinization process and sodisation if the question of liming is resolved technically and economically. The work aims to study the effect of two types of amendments on the physicochemical and hydric characteristics in a salty soil of the experimental station of INRAA El Hmadena (Relizane). The results show that the amendment doses gypsum and DS advocated affect very slightly different physicochemical and water indicators of the studied soils. Changes in these indicators are very exposed area between the horizons, intermediate and lower soil profile.
Keywords: salinization; sodisation; gypsum amendment; salsodic soil; soil quality indicators; salinisation; sodisation; amendement gypseux; sol salsodique; indicateurs de qualité des sols.